Matthew Tindal i redukcja chrześcijaństwa do religii naturalnej - Szwed, Antoni (Humaniora. Czasopismo Internetowe, 2020)
In his Christianity as Old as the Creation Matthew Tindal has reduced Christian religion to the natural religion. His reduction was the last stage of purification of Protestant religion from its supernatural elements. This whole process was taking place in England between 1534 and 1730. The main conclusion of this English deist sounded: the revealed religion was the only repetition of the eternal natural religion, based on the law of nature and human reason. Simultaneously he claimed that any Christian proprium (specific Christian content) did not exist in relation to any other non Christian religion. In this article I put this problem through critical assesment, making analysis of Tindal’s argumentation and confronting it with (to some degree) Thomas Becconsall views, expressed in his The Grounds and Foundation of Natural Religion. In contrast to Becconsall Tindal understands the nature of man in another way. This latter rejects the opinion that human nature was burdened with certain moral ineffectuality. According to it human being is more prone to misdeeds than to good deeds. In Christian religion it was possible to explain by the original sin and its hereditary effects in the history of mankind. Matthew Tindal rejects this Christian dogma. In reality he understands man’s existence in the state of pure nature and with reason acting without limitations. It corresponds to the situation of man before the Fall into the original sin. But Tindal is not any atheist. He is convinced of God’s existence as the Creator of the world and people. The reason of human beings participates in the light of Divine Wisdom. Thus cognition of God and human moral duties are possible (in practice) by intellectual effort directed to the sensible creatures only. This kind of rational investigation is characteristic for methaphysical cognition. In fact, there is small step from deism to atheism. English Enlightenment, based on the enlightened reason, was initially deistic character, afterwards on the Continent (especially in France) it quickly assumed atheistic form. In considerable degree it was possible owing to English deists like Matthew Tindal. They draw the ultimate conclusion from the plurality of Protestant denominations.